Analysis of the probability of rainfall in the Fingeshwar Tehsil of the Gariyaband District for crop planning - Rajendra Kumar Deo; B.L. Sinha (Environment Conservation Journal, 2023)
Rainfall probability analysis improves predictions of the minimum assured rainfall to aid crop planning. An attempt has been made to look into the patterns of rainfall distribution, including weekly, seasonal, and annual rainfall, using data collected from the Fingeshwar tehsil of the Gariyaband district, Chhattisgarh, over a ten-year period (2011-2020). Using the Weibull plotting position function, expected weekly, monthly, seasonal, and yearly rainfall values were calculated for various probability levels. Based on a 10-year yearly average, the data revealed that 1074.4 mm of rain were actually seen, following an average of 52.2 rainy days. A rainfall amount with a 75% probability level predicts 862.9 mm annually. The largest amount of weekly rainfall, 49 mm, was predicted to fall in the 35th week, followed by 32.1 mm in the 25th standard week and the least amount, 0.0 mm, in the 20-22nd, 29, 37, 40-42nd SMW. This prediction was made at a 75% chance level, same like the one before. According to a study of monthly rainfall at 70, 75, and 80% probability levels, the three crucial wet months are July, August, and September, with probabilities of getting a monthly rainfall between 0 and 50 mm. At a 70% probability level, the seasonal rainfall report projects 833 mm for the Kharif season. Thus, it can conclude that the kharif season's activities could start between the 22nd and the 23rd standard week and farmers can properly produce paddy crops in highland areas followed by any rabi crop in rabi season.